2020
DOI: 10.1108/arch-11-2019-0258
|View full text |Cite
|
Sign up to set email alerts
|

A life cycle assessment of a ‘minus carbon’ refugee house: global warming potential and sensitivity analysis

Abstract: PurposeOver the last eight years, the Middle East has experienced a series of high profile conflicts which have resulted in over 5.6 million Syrians forced to migrate to neighbouring countries within the MENA (Middle East and North Africa) region or to Europe. That have exerted huge pressure on hosting countries trying to accommodate refugees in decent shelters and in quick manner. Temporary shelters normally carry a high environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…From a technical-experimental perspective, the work of Dabaieh et al (2020) assesses the carbon impact for a minus carbon experimental refugee house in Sweden, utilising life cycle assessment as a tool for this experiment. The results demonstrate that using local plant-based materials such as straw, reeds and timber together with clay dug from the vicinity of the construction site can significantly reduce the carbon footprint of temporary shelters, while SDGs-centred architectural pedagogies further attaining a negative carbon impact of 226.2 kg CO 2 eq/m.…”
Section: The Knowledge Space Of Architectural and Urban Sustainabilit...mentioning
confidence: 99%
See 1 more Smart Citation
“…From a technical-experimental perspective, the work of Dabaieh et al (2020) assesses the carbon impact for a minus carbon experimental refugee house in Sweden, utilising life cycle assessment as a tool for this experiment. The results demonstrate that using local plant-based materials such as straw, reeds and timber together with clay dug from the vicinity of the construction site can significantly reduce the carbon footprint of temporary shelters, while SDGs-centred architectural pedagogies further attaining a negative carbon impact of 226.2 kg CO 2 eq/m.…”
Section: The Knowledge Space Of Architectural and Urban Sustainabilit...mentioning
confidence: 99%
“…From a technical-experimental perspective, the work of Dabaieh et al . (2020) assesses the carbon impact for a minus carbon experimental refugee house in Sweden, utilising life cycle assessment as a tool for this experiment.…”
Section: Architectural Pedagogy and Sustainability – Two Growing Know...mentioning
confidence: 99%
“…Their findings assert that visual communication by engineers increases the level of technical knowledge in design decisions made by architects and that this would enable designing buildings with low environmental impact while maximizing acceptance of the architects' proposals by the engineers. The work of (Dabaieh et al ., 2020) assesses the carbon impact for a minus carbon experimental refugee house in Sweden using life cycle assessment (LCA) as a tool for this experiment. The results demonstrate that using local plant-based materials such as straw, reeds and timber, together with clay dug from nearby the construction site, can significantly reduce the carbon footprint of temporary shelters and can further attain a negative carbon impact of 226.2 kg CO 2 eq/m 2 .…”
Section: Preliminary Characterization Of Evolving Knowledge Spacesmentioning
confidence: 99%
“…Moreover, from 2011 till now, Kurdish from Syria live as refugees in KRI [7]. The majority of migrants live in inefficient and uncomfortable transitional and temporary shelters this normally carries a high burden on the environment and host countries and cost billions of dollars for establishing due to the short lifespan of that shelters [8,9]. Currently, all advanced countries focused on building energy problems in different ways to use energy rationally and to preserve it is sources [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wagemann [21] investigated in research titled From Shelter to Home different strategies for flexibility in post-disaster accommodation through movable buildings, design and construction methods. Rincon et al [22] analyzed and simulated the thermal behavior of dome shape earth-bag building in the Mediterranean climate in the same way, another study assessed the carbon impact of migrants shelters and resulted that using local materials like straw, wood, and clay, can extremely decrease the carbon footprint [8]. Ibrahim et al [23] observed the superiority of the adobe dome over other humanitarian agencies shelters as tent caravans in northern Syria through analyzed and compared based simulated research.…”
Section: Introductionmentioning
confidence: 99%